Comparison of the intravenous and intravaginal route of oxytocin administration for cervical dilation protocol and non-surgical embryo recovery in oestrous-induced Santa Ines ewes - Prellwitz, Lucia; Zambrini, Fabiana Nunes; Guimaraes, Jose Domingos; Paula de Sousa, Marco Antonio; Franco Oliveira, Maria Emilia [UNESP]; Garcia, Alexandre Rosetto; Esteves, Sergio Novita; Bartlewski, Pawel Mieczyslaw; Goncalves Souza-Fabjan, Joanna Maria; Fonseca, Jeferson Ferreira (Wiley-Blackwell, 2019)
This study compared the effects of intravaginal and intravenous routes of oxytocin (OT) administration in 46 oestrous-induced Santa Ines ewes (6-day treatment with progestin-releasing intravaginal sponges and a single injection of 200 IU of eCG at the time of sponge removal) that underwent transcervical embryo recovery 6-7 days after oestrous onset and mating. All ewes received 37.5 mu g of d-cloprostenol via latero-vulvar route, and 1 mg of oestradiol benzoate i.m. 16 hr before and 50 IU of OT 20 min before non-surgical embryo recovery (NSER), with OT being administered intravenously (n = 21) or intravaginally (n = 21). An overall oestrous response was 95.6% (44/46), and adequate cervical retraction could be accomplished in 78.6% (33/42) of ewes. The percentage of successful NSER procedures was 57% (24/42) or 72.7% (24/33) of animals with sufficient cervical retraction. The duration of NSER procedure averaged 28 min (range: 17-40 min) and similar to 96% of flushing fluid could be recovered (range: 85%-100%). Out of 18 ewes that could not undergo NSER, 12 (66.6%) presented various anatomical barriers, whilst the other 33.4% did not present these barriers and still could not be traversed. Excluding the ewes with those anatomical features, the overall success rate of NSER was 80% (24/30). The route of OT administration had no effect on NSER efficiency or the ease with which transcervical embryo flushing was performed. Both routes of OT administration can be used for cervical dilation protocol. Discarding ewes with anatomical features precluding cervical penetration is highly recommended to increase the efficacy of NSER in sheep.
Keywords: cervical relaxation; sheep; transcervical embryo collection; uterine flushing